Pitfalls in phenylalanine loading test in the diagnosis of dopa-responsive dystonia - Opladen, Thomas; Hoffmann, Georg F.; Kühn, Andrea; Blau, Nenad (Molecular genetics and metabolism, 2013)
Phenylalanine (Phe) loading test is a useful tool in the differential diagnosis of dopa-responsive dystonia due to autosomal dominant or recessive GTP cyclohydrolase I (GTPCH) deficiency or autosomal recessive sepiapterin reductase (SR) deficiency. In these patients hepatic phenylalanine hydroxylase system is compromised due to subnormal tetrahydrobiopterin (BH4) levels and hydroxylation of phenylalanine (Phe) to tyrosine (Tyr) is reduced with elevated Phe/Tyr ratio 1-2h after oral Phe administration (100mg/kg bw) administration. In healthy persons there is only a modest increase in Tyr production and blood Phe normalizes after 4h. We report on a challenge with Phe (100mg/kg bw) in a patient with dopa-responsive dystonia while on therapy with BH4 and l-dopa. During Phe challenge Phe concentration remained below the normal range while a transient mild hypertyrosinemia was observed, leading to an extremely low Phe/Tyr ratio. A repeated test, after BH4 withdrawal, reversed the findings and resulted normal. These data suggest activation of hepatic phenylalanine hydroxylase by BH4. Thus, the Phe loading test should not be performed during substitution with BH4.